CRYPTOCURRENCY FROM MAQĀṢID AL-SHARĪ‘AH PERSPECTIVE: REGULATORY COMPARISON OF INDONESIA AND MALAYSIA - nisha hafizo; Aida Humaira; Mualimin Mochammad Sahid (MAQASHID, 2026)
This research interrogates cryptocurrency as a quintessential paradigm of contemporary digital financial innovation, evaluated through the analytical prism of maqāṣid al-sharī‘ah. It fundamentally scrutinizes the normative implications of decentralized digital assets within the ambit of Islamic legal philosophy, particularly concerning the preservation of public interest (maṣlaḥah) and the mitigation of systemic harm (dar’ al-mafāsid). Central to this inquiry is the evaluation of cryptocurrency’s intrinsic characteristics against the core Shariah objective of wealth preservation (ḥifẓ al-māl). Building upon this normative foundation, the study executes a comparative jurisprudential and regulatory analysis of the frameworks operative in Indonesia and Malaysia. This comparison aims to elucidate the divergent trajectories through which sovereign Muslim-majority jurisdictions internalize the ethical and legal complexities of blockchain-based instruments into their national financial architectures. Methodologically, this study adopts a qualitative descriptive design predicated on extensive documentary analysis. The research corpus encompasses a synthesis of statutory instruments, directives from financial supervisory authorities, authoritative Shariah pronouncements (fatāwā), classical and contemporary fiqh literature, and peer-reviewed academic discourse. The findings reveal a dualistic nature of cryptocurrency: while offering substantial technological utility, it harbors inherent risks, specifically volatility-induced uncertainty (gharar) and speculative excess (maysir), that necessitate a robust prudential framework. Furthermore, the comparative findings delineate a methodological schism: Indonesia utilizes a commodity-based administrative model, whereas Malaysia adopts an integrated capital market regime. These distinctions reflect nuanced sovereign strategies in operationalizing maqāṣid principles within distinct institutional contexts. The study concludes that an integrated, maqāṣid-oriented regulatory paradigm is imperative to harmonize technological acceleration with the ethical mandates of Islamic law, ensuring financial stability and investor protection in the digital era. Keywords: Cryptocurrency, Maqāṣid al-Sharī‘ah, Comparative Jurisprudence, Regulatory Policy, Islamic Finance, Indonesia, Malaysia.